Penerapan Inovasi Manajemen Sarana Dan Prasarana Untuk Mendukung Pembelajaran Berbasis Digital Pada Sekolah - Isroful Jannah; Mei Wiji Astuti; Ika Sofa Sofiana (Sekolah Tinggi Agama Islam Muhammadiyah Blora, 2025)
The development of information and communication technology has brought significant changes to the world of education, particularly at the elementary school level. Digital transformation encourages educational institutions to innovate in the management of facilities and infrastructure to support the effectiveness of technology-based learning. This study aims to analyze the concept, urgency, forms of innovation, challenges, and the impact of the implementation of facilities and infrastructure management on the effectiveness of digital learning in elementary schools. The research method used is library research by reviewing various literature such as books, scientific journals, and relevant articles from the past five years. The results show that innovation in facilities and infrastructure management plays a crucial role in creating an effective, efficient, and adaptive learning environment to technological developments. The forms of innovation implemented include the use of a digital inventory management system, the implementation of smart classrooms, the development of interactive learning media, and the utilization of school management information systems. However, in its implementation, elementary schools still face various obstacles, including budget constraints, a lack of teacher competency in using technology, and weak supporting infrastructure. Nevertheless, the implementation of planned and sustainable innovation has been proven to improve learning effectiveness, active student engagement, and school management efficiency. Thus, innovation in facility and infrastructure management becomes a strategic factor in realizing quality and competitive digital learning in the modern education era.